First case report on pathogenic fungus Fonsecaea sp. Negroni from skin of Pelophylax kl. esculentus L. in Serbia - Stupar Miloš Č.; Breka Katarina V.; Krizmanić Imre I.; Stamenković Srđan Z.; Unković Nikola D.; Savković Željko D.; Vukojević Jelena B.; Ljaljević-Grbić Milica V. (Zbornik Matice Srpske za Prirodne Nauke, 2017)
Non-harmful adhesive tape method was applied directly on the skin surface of edible frog (Pelophylax kl. esculentus), captured in vernal ponds on the locality “Stevanove ravnice” within the Special Nature Reserve „Deliblatska peščara“, in order to detect fungal dwellers of frogs’ skin. Light microscopy analyses of Lactophenol Cotton Blue mounted adhesive tape samples taken from frog’s ventrum revealed the presence of melanized septate hyphae, branched conidiophores with chains of single-celled ovoid conidia, arising directly from the skin, which corresponds to morphological features of dematiaceous hyphomycete - Fonsecaea sp. Since members of genus Fonsecaea are frequently cited as causative agents of chromomycosis in amphibians, as well as human phaeohyphomycosis, worldwide, it is of great significance to study the presence of this fungal pathogen on amphibians in Serbia in order to make the basic reference data of the incidence of these pathogens in this region. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 173032]